"GUESSING NUMBERS" GAMBLING IN SURABAYA IN THE 1950-1980S - Mawardi Purbo Sanjoyo (SOLIDARITY: Journal of Social Studies, 2022)
Gambling games in Indonesia have been going on for a long time, even before the Dutch colonial presence in Indonesia gambling games had become part of the activities of the Javanese people in the 11th century. In its development, the types of gambling games are increasingly diverse, such as the money lottery, goods lottery, Hwa-Hwee and Lotto in Surabaya. The role of the government was also a driving force for the rise of gambling games in Surabaya in the 1950-1980s because of the legalization of gambling. The real purpose of legalization is to get taxes from gambling games and be able to overcome social problems in Surabaya. Although in this case not all gambling games are strictly monitored by the local government, it means that there are also illegal gambling games. The purpose of this study was to determine the activities and developments of gambling in Surabaya in the 1950s to the 1980s and what the impact of gambling activities was in Surabaya. To find out how the development and impact of gambling in Surabaya, researchers use an economic and social approach by presenting historical data from newspapers, magazines, archives, and other scientific works.